Fingolimod reduces circulating tight-junction protein levels and in vitro peripheral blood mononuclear cells migration in multiple sclerosis patients. Issue 1 (December 2018) - Annunziata, Pasquale; Cioni, Chiara; Masi, Gianni; Tassi, Maristella; Marotta, Giuseppe; Severi, Sauro
Abstract There are no data on the effects of fingolimod, an immunomodulatory drug used in treatment of multiple sclerosis (MS), on circulating tight-junction (TJ) protein levels as well as on peripheral blood mononuclear cells (PBMC) migration. Serum TJ protein [occludin (OCLN), claudin-5 (CLN-5) and zonula occludens-1 (ZO-1)] levels, sphingosine-1 phosphate 1 (S1P1 ) receptor expression on circulating leukocyte populations as well asin vitro PBMC migration were longitudinally assessed in 20 MS patients under 12-months fingolimod treatment and correlated with clinical and magnetic resonance imaging (MRI) parameters. After 12 months of treatment, a significant reduction of mean relapse rate as well as number of active lesions at MRI was found. TJ protein levels significantly decreased and were associated with reduction of S1P1 expression as well as of PBMCin vitro migratory activity. A significant correlation of CLN-5/OCLN ratio with new T2 MRI lesions and a significant inverse correlation of CLN-5/ZO-1 ratio with disability scores were found. These findings support possiblein vivo effects of fingolimod on the blood-brain barrier (BBB) functional activity as well as on peripheral cell trafficking that could result in avoiding passage of circulating autoreactive cells into brain parenchyma. Circulating TJ protein levels and respective ratios could be further studied as a novel candidate biomarker of BBB functional status to be monitored in course of fingolimod as well as of other immunomodulatory treatments in MS.